Grain Configuration Effect on Pore Water Pressure in Debris Flow - Yang, Taiqiang; Liu, Daochuan; Li, Yong; Guo, Xiaojun; Zhang, Jun; Jiang, Yu (Frontiers in Earth Science, 2021)
The generation and development of excess pore water pressure directly affects the grain interaction in debris flow, which can significantly reduce the friction strength and promote the movement of debris flow. It has been found that coarse grains favor the increase in excess pore water pressure, but the effect due to grain configuration is missing in studies. In order to study the influence of grain configuration, field investigations and laboratory tests were carried out for two typical cases, i.e., flow with coarse grains evenly mixed (case I) and flow with coarse grains floating on the surface (case II). The results show that case II generates much higher excess pore water pressure than case I. The variation of relative excess pore water pressure (Ur) with time (t) satisfies the power function relationship: Ur = mt–n. Case II often has a smaller n value, meaning a low dissipation rate of excess pore water pressure. This study is helpful for a better understanding of granular effects in debris flow.